(3CKQ GdYjH aj GdeYGedGJ GdeGdjI (B:s (3OQGSI ebGQfI Hjf Gdabg GdGSdGej h GdbGfhf GdeOfj (B/s - (3YRGe, WGQb UGdM jhSas ((3YeGf(B: s (3OGQ GdfaGFS(B, s, 2009)
1) (3JYQja NjGQ GdYjH h eTQhYjJg h JHjjf Mce GdYbO eY NjGQ GdYjH h TQGFW GdQO h cjajJg h WQb GKHGJg , ehGfY GdQO HGdYjH , GfJbGd NjGQ GdYjH Gdi GdhQKI Ce dG h eOI gPG GdNjGQ (B2) (3CMcGe XeGf GdYjH (B: (3GdVeGf h eTQhYjJg h CSHGHg h MGdGJg h TQhW GdYjH , TQhW KHhJ GdYjH , JbOjQ VeGf GdYjH h CNjQG eSbWGJ VeGf GdYjHs
Keywords: (3GdGbJUGO GdGSdGejs; (3Gdabg GdGSdGejs; (3GdbGfhf GdeOfjs; (3GdeYGedGJ (B((3abg GSdGej (B)s